Activated leukocyte cell adhesion molecule (ALCAM) is a marker of recurrence and promotes cell migration, invasion, and metastasis in early‐stage endometrioid endometrial cancer. Issue 4 (23rd January 2017) - Devis, Laura; Moiola, Cristian P; Masia, Nuria; Martinez‐Garcia, Elena; Santacana, Maria; Stirbat, Tomita Vasilica; Brochard‐Wyart, Françoise; García, Ángel; Alameda, Francesc; Cabrera, Silvia; Palacios, Jose; Moreno‐Bueno, Gema; et al.
Abstract: Endometrial cancer is the most common gynaecological cancer in western countries, being the most common subtype of endometrioid tumours. Most patients are diagnosed at an early stage and present an excellent prognosis. However, a number of those continue to suffer recurrence, without means of identification by risk classification systems. Thus, finding a reliable marker to predict recurrence becomes an important unmet clinical issue. ALCAM is a cell–cell adhesion molecule and member of the immunoglobulin superfamily that has been associated with the genesis of many cancers. Here, we first determined the value of ALCAM as a marker of recurrence in endometrioid endometrial cancer by conducting a retrospective multicentre study of 174 primary tumours. In early‐stage patients ( N = 134), recurrence‐free survival was poorer in patients with ALCAM‐positive compared to ALCAM‐negative tumours (HR 4.237; 95% CI 1.01–17.76). This difference was more significant in patients with early‐stage moderately–poorly differentiated tumours (HR 9.259; 95% CI 2.12–53.47). In multivariate analysis, ALCAM positivity was an independent prognostic factor in early‐stage disease (HR 6.027; 95% CI 1.41–25.74). Then we demonstrated in vitro a role for ALCAM in cell migration and invasion by using a loss‐of‐function model in two endometrial cancer cell lines. ALCAM depletion resulted in a reduced primary tumour size and reduced metastatic local spread in an orthotopic murine model. Gene expression analysis of ALCAM‐depleted cell lines pointed to motility, invasiveness, cellular assembly, and organization as the most deregulated functions. Finally, we assessed some of the downstream effector genes that are involved in ALCAM‐mediated cell migration; specifically FLNB, TXNRD1, and LAMC2 were validated at the mRNA and protein level. In conclusion, our results highlight the potential of ALCAM as a recurrent biomarker in early‐stage endometrioid endometrial cancer and point to ALCAM as an important molecule in endometrial cancer dissemination by regulating cell migration, invasion, and metastasis. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.